Cocrystallization in vitamin B9 gels to construct stoichiometry-controlled isostructural materials. Issue 12 (13th February 2018) - Bao, Junjie; Zhang, Zaiyong; Yan, Zhicheng; Wang, Jian-Rong; Mei, Xuefeng
Abstract : The potential application of structurally equivalent Cl, Br, and I in the design of isostructural materials in VB9 gels is illustrated by constructing pairs of solids that exhibit different fluorescence properties. Abstract : Six new cocrystals of acridine were designed and synthesized by stoichiometry-controlled cocrystallization in vitamin B9 gels. The potential application of structurally equivalent Cl, Br, and I in the design of isostructural materials is illustrated by constructing pairs of solids that exhibit different fluorescence properties.